International Business / Environments, Institutions, and Operations - Beeman Don R.; Taoka George M (Harper Collins Publishers, 1991)
Preface, The Nature and Importance and Bases for International Business, The Development and Importance of World Trade and Investment and the Multinational Firm (MNF), Theories, The International Environment for International Business, International Agreements to Minimize Conflicts, Foreign Exchange, The International Monetary System and the Balance of Payments, International Business and the Role of Financial Institutions, The Intranational Environment of International Business, Commercial Policies and Instruments for Protection, Geographic Environment, Political and Legal Considerations in International Business, Economic Environment, The Human and Cultural Environment of International Business, Functions of International and Multinational Firms, Strategies and Structures of International Firms, International Marketing Strategy, Trends and the Future of International Business, Prospects for the Future of International Business, Glossary, Index.
Preface, The Nature and Importance and Bases for International Business, The Development and Importance of World Trade and Investment and the Multinational Firm (MNF), Theories, The International Environment for International Business, International Agreements to Minimize Conflicts, Foreign Exchange, The International Monetary System and the Balance of Payments, International Business and the Role of Financial Institutions, The Intranational Environment of International Business, Commercial Policies and Instruments for Protection, Geographic Environment, Political and Legal Considerations in International Business, Economic Environment, The Human and Cultural Environment of International Business, Functions of International and Multinational Firms, Strategies and Structures of International Firms, International Marketing Strategy, Trends and the Future of International Business, Prospects for the Future of International Business, Glossary, Index.